PENGARUH BUDAYA SEKOLAH 5S TERHADAP PEMBENTUKAN KARAKTER ISLAMI SISWA DI SMP A. WAHID HASYIM TEBUIRENG JOMBANG - Hamdiyah, Liwa’ul; Jumari, Jumari (EL-Islam, 2023)
Abstract: This article examines the school culture of smiles, greetings, greetings, politeness, and courtesy (5S) as values, principles, and traditions that have been formed in the long journey of the school. This culture was developed by the school over a long period of time and became a guideline for all school members, so it gave birth to the attitudes and behavior of school members, namely smiling, greeting, greeting, politeness, and manners (5S). With the application of the 5S school culture, it will form an Islamic character that exists in students. Islamic character is a trait that is inherent in a student in the form of a person's character, character, and morals that are Islamic or easy morals. From this study, it can be seen that there is an influence of the 5S school culture (smiles, greetings, greetings, politeness, and courtesy) on the formation of the Islamic character of students at SMP A. Wahid Hasyim Tebuireng Jombang. This study uses the type of ex post facto, that the independent (independent) variables have occurred, when it begins with the observation of the dependent (dependent) variable in a research study. In this study, it was produced, that the results of the hypothesis testing were obtained with a sig. 0.335. The sig value obtained is > 0.05 so the accepted hypothesis is H0 and Ha is rejected. Thus, there is an influence from the application of the 5S school culture on the formation of Islamic character in SMP A. Wahid Hasyim Tebuireng Jombang.